Falling trade costs, heterogeneous firms and industry dynamics - Andrew Barnes Bernard; J. Bradford Jensen; Peter K. Schott (Institute for Fiscal Studies (IFS), 2003)
This paper examines the response of industries and firms to changes in trade costs. Several new firm-level models of international trade with heterogeneous firms predict that industry productivity will rise as trade costs fall due to the reallocation of activity across plants within an industry. Using disaggregated U.S. import data, we create a new measure of trade costs over time and industries. As the models predict, productivity growth is faster in industries with falling trade costs. We also find evidence supporting the major hypotheses of the heterogenous- firm models. Plants in industries with falling trade costs are more likely to die or become exporters. Existing exporters increase their shipments abroad. The results do not apply equally across all sectors but are strongest for industries most likely to be producing horizontally-differentiated tradeable goods.
Keywords: F10; 330; Plant deaths; survival; exit; exports; employment; tariffs; freight costs; transport costs; Produktivität; Transaktionskosten; Außenwirtschaft; Preiswettbewerb; Industrieökonomik; Theorie